2012
DOI: 10.1186/1471-2164-13-509
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of peritoneal cells in a mouse model of sepsis: confirmatory and novel results in early and late sepsis

Abstract: BackgroundThe events leading to sepsis start with an invasive infection of a primary organ of the body followed by an overwhelming systemic response. Intra-abdominal infections are the second most common cause of sepsis. Peritoneal fluid is the primary site of infection in these cases. A microarray-based approach was used to study the temporal changes in cells from the peritoneal cavity of septic mice and to identify potential biomarkers and therapeutic targets for this subset of sepsis patients.ResultsWe cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Previous study has demonstrated that Ebf1 expression was significantly upregulated in the early stages of sepsis (Bhatty et al. 2012 ). Intriguingly, Ebf1 mRNA was reported to be regulated by multiple altered miRNAs in a rat model of ARDS (Huang et al.…”
Section: Discussionmentioning
confidence: 94%
“…Previous study has demonstrated that Ebf1 expression was significantly upregulated in the early stages of sepsis (Bhatty et al. 2012 ). Intriguingly, Ebf1 mRNA was reported to be regulated by multiple altered miRNAs in a rat model of ARDS (Huang et al.…”
Section: Discussionmentioning
confidence: 94%
“…Ebf1 is a transcription factor, which is important for early B cell development (Gao et al 2009). Previous study has demonstrated that Ebf1 expression was signi cantly upregulated in the early stages of sepsis (Bhatty et al 2012). Intriguingly, Ebf1 mRNA was reported to be regulated by multiple altered miRNAs in a rat model of ARDS (Huang et al 2014).…”
Section: Discussionmentioning
confidence: 95%
“…Ebf1 is reported to be expressed in several CNS regions and has been implicated in CNS function and development [ 102 105 ]. This factor has also been implicated in B-cell development and peripheral inflammation [ 106 108 ]. Furthermore, Ebf1 may exert a role in the pathophysiology of multiple sclerosis [ 109 ].…”
Section: Discussionmentioning
confidence: 99%